KAJIAN TEKSTOLOGIS TERHADAP MANUSKRIP MUSHAF AL-QUR’AN 07.13 DI MUSEUM SANG NILA UTAMA PEKANBARU - Nahdatul Fitri; Syifa Qalbina Izzah S; Yulan Permata sari; Zazkia Fara Dinda R; Wardatul Aini; Lukmanul Hakim (Makkah: Journal Of Islamic Studies, 2025)
This study examines the textological approach applied to the manuscript of the Qur’anic mushaf coded 07.13 preserved at the Sang Nila Utama Museum, Pekanbaru, Riau. The research is motivated by the urgency of preserving classical Qur’anic manuscripts as cultural and religious heritage that reflects the development of Islamic scholarship in the Malay world. Using a qualitative descriptive method, the manuscript is analyzed through philological and textological perspectives, including codicological elements, writing characteristics, calligraphy style, orthography, and textual variants. The theoretical foundation of this study derives from philological approaches in Islamic manuscript studies, particularly those emphasizing textual authenticity and variant comparison. The findings reveal that Mushaf 07.13 displays distinctive features of Malay manuscript traditions, such as the use of traditional Arabic calligraphy with local stylistic adaptations and consistent rasm ‘Uthmānī orthography. Several minor orthographical deviations are recorded, which enrich understanding of regional Qur’anic transmission practices. This research concludes that the textological examination of Mushaf 07.13 highlights the importance of continuous preservation and scholarly documentation of Qur’anic manuscripts in regional museums as part of safeguarding Islamic intellectual heritage.